MGTClick - Mohd Salim, Nor Zarina; Ithnin, Hafini Suhana; Mohd Helmy, Muhammad Aiman Najmy; Mohd Yusoff, Nurul Shazwani; Abd. Rasid, Nur Mashitah (2022)
Online Distance Learning (ODL) has become a new norm of teaching since Covid-19 hit the world 2 years ago. This situation gives some challenges and creates new pressure towards students as well as lecturers. Thus, MGTClick is an online system that was developed to help Pra Pendidikan Tinggi (PPT) students who enrolled in MGT028 (Introduction to Business) to manage, monitor as well as to plan one of their subjects. The purpose of this study is to facilitate PPT students to organize their study and reduce their pressure in managing each folder, links and application involved in one subject. While using this MGTClick it will help students to gather all the information about that subject under one roof. It only required one click for students to access relevant information regarding that subject. However, this application needs to collect all the information manually tin order to create a new link for the selected files. Finally, all the links will be joined together in domain home. Hence, it is hoped that this application will give some value to lecturers and PPT students who are totally new with the university system and to reduce missing information.